Effect of the sintering temperature on the microstructure and superconducting properties of MgB2 bulks manufactured by the field assisted sintering technique - Matthews, GAB; Santra, S; Ma, R; Grovenor, C; Grant, V; Speller, S (IOP Publishing, 2020)
Magnesium diboride (MgB2) bulk superconductors may have practical applications as permanent magnets owing to their ability to trap larger fields than conventional ferromagnets and a transition temperature of 39 K that make them attractive for use in cryogen-free systems. Unlike the cuprate high temperature superconductors, grain boundaries in MgB2 act as pinning sites not weak links, and so show good current carrying ability in polycrystalline samples. This enables the materials to be processed using standard ceramic processing methods which are scalable to large diameters and mass production. The maximum trapped field in bulk superconductors scales with the critical current density (Jc ) of the material as well as the radius of the sample. To obtain the highest possible Jc values in MgB2 at high fields requires the bulk materials to be fully dense but fine-grained material, and possibly with a nano-scale distribution of non-superconducting impurity particles to further enhance pinning. Field assisted sintering technology (FAST) is a rapid process for obtaining dense ceramics from materials like MgB2 which are difficult to sinter with conventional pressure-less techniques. Rapid heat treatments are attractive both from a manufacturing point of view and because the total time that the sample is held at high temperature is short, limiting grain coarsening. In this paper, we report a systematic study of the influence of processing temperature on microstructure and superconducting properties of MgB2 bulks manufactured using FAST. We conclude that processing temperatures above 1000 °C are required to obtain materials that have sufficiently high electrical connectivity to generate large magnetic moments. However, the intrinsic (intragrain) Jc values in MgB2 are better in the samples processed at 900 °C owing to their finer scale microstructures and the MgB2 lattice being more defective.